Alterações fisiológicas, bioquímicas e moleculares em sementes de seringueira [Hevea brasiliensis (Willd. ex Adr. de Juss.) Muell.-Arg.] durante o armazenamento - Bonome, Lisandro Tomás da Silva (2006)
The difficulty of storing rubber seeds is one of the main hindrances to seedling production in a commercial scale in the "escape" regions, which are regions of low temperature and relative humidity not favorable to the development of the Microcyclus ulei causer of the South American leaf blight. Studies about the physiological, biochemical and molecular alterations in rubber seedlings during storage can elucidate the causes of the fast loss of viability of those seeds, even when placed in conditions ideal to their conservation. The present research was developed in the Plant Nutrition and Metabolism Laboratory in the Biology Department jointly with the Laboratories of Seed Analysis and Molecular Techniques of the Agriculture Department of the Federal University of Lavras, with the objective of evaluate and relating the modifications occurring in rubber seeds packed in waterproof package, treated or not with fungicides Tecto 600 (65g/100Kg seed) and Captan (135g/100kg seeds) in two settings (cold chamber at 10oC and room condition ± 20oC), for a 210-day period of storage. In different periods of storage, the seeds were submitted to determinations of physiological characteristics, cell characteristics by light and scanning electron microscopy, biochemical and molecular characteristics. The best conditions for rubber seed keeping were at room temperature without any fungicide treatment. The fungicide treatment had a phytotoxic effect upon the seeds. The temperature of 10oC was also harmful to the storage of the rubber seeds causing more severe damages to their physiological quality. The association between the fungicide treatment and low temperature of storage was potentially more harmful to the preservation of seeds tan the factors utilized singly. Significant alterations took place in the content of starch, soluble and reducing sugars, proteins and aminoacids both in the embryo and in the endosperm of the rubber seeds over storage, independent if treated or not with fungicides of the environmental conditions. In the embryo biosynthesis of lipids occurred over the storage, likely fro the finishing of its maturation. But in the endosperm, degradation of lipids was observed over the storage. The occurrence of lipid peroxidation was still noticed in the first months of storage, chiefly when the seeds were packed at low temperature. Variations in the electrophoresis profile of isoenzimes are associated with the deteriorative process of rubber seeds. The enzymes alcohol dehydrogenase, esterase, glutamate-oxaloacetate transaminase, superoxide dismutase, catalase and peroxidase revealed themselves as promising indicators for the evaluation of rubber seed deterioration. (Project partially supported by CNPq).